Evaluation of $$\int^{\infty}_{0}e^{-ax}(\cos x)^ndx,a>0$$

$\bf{My\; Try::}$ Let $$I = \int^{\infty}_{0}e^{-ax}(\cos x)^ndx\;,$$

Now Using euler substution $$\cos x = \frac{e^{-ix}+e^{-ix}}{2}$$

So $$I = \int^{\infty}_{0}e^{-ax}\left(\frac{e^{ix}+e^{-ix}}{2}\right)^ndx$$

Now Use Binomial expansion,But i did not understand how can i solve after that, Help required


  • $\begingroup$ you can integrate $e^{-ax}cos(bx)$ by using integration by parts twice, then rearranging in terms of your original integral, which will then appear on the left and right hand sides. you could use the $(\frac{e^{-ix}+e^{-ix}}{2})^n$ expansion to get an expression for $(cos(x))^n$ in terms of a cos bx with various a and b $\endgroup$ – Cato Oct 11 '16 at 9:30

Hint: $$\int_0^\infty e^{(-a+in)x}dx=\frac{1}{-a+in}e^{(-a+in)x}\Big|_0^\infty=\frac{1}{in-a}$$ Of course, assuming that $a>0$.


Let $I_{n}=\int_{0}^{\infty}e^{-ax}(cos(x))^ndx$

Then we know that $I_{0}=1/a$, and $I_{1}=-a/(1+a^2)$

Now, using integration by parts,


$=e^{-ax}(cos(x))^{n-1} sin(x)|_{0}^{\infty} - \int_{0}^{\infty}[e^{-ax}.(-a)(cos(x))^{n-1}-e^{-ax}.(cos(x))^{n-2}.(n-1).sin(x)](\int cos(x) dx) dx$

$=0 + a\int _{0}^{\infty}e^{-ax}.(cos(x))^{n-1}.sin(x)dx + (n-1) \int_{0}^{\infty}e^{-ax}.(cos(x))^{n-2}(1-cos^{2}(x)) dx$

$=a\int _{0}^{\infty}e^{-ax}.(cos(x))^{n-1}.sin(x)dx + (n-1)(I_{n-2}-I_n)$

$=a[(e^{-ax}\int (cos(x))^{n-1}.sin(x)dx)|_{0}^{\infty} -\int_{0}^{\infty} (-a).e^{-ax}(\int (cos(x))^{n-1}.sin(x)dx)dx] + (n-1)(I_{n-2}-I_n)$

$= -a/n + (a^2/n)I_n + (n-1)(I_{n-2}-I_n)$

So we have

$I_n = -a/n + (a^2/n)I_n + (n-1)(I_{n-2}-I_n)$

which gives us


This is a recursive relation and gives a formula for $I_n$ in $I_{0}$ for n even and $I_1$ for n odd.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.